Knowledge, Attitudes, and Practices Regarding Brucellosis among the General Population in Hafar Al-Batin, Saudi Arabia: An Analytical Cross-Sectional Study - Hossam Mohammed Yousef; Nasser Truki Aldhaferi; Tami Heleil Aldhaferi; Alsadig Alsayed Modawi; Mashari Benian Alenazi (IPS Journal of Public Health, 2026)
Background: Brucellosis remains an endemic zoonosis in Saudi Arabia, where livestock husbandry, direct animal contact, and consumption of unpasteurized dairy products sustain preventable human exposure. Community knowledge, attitudes, and practices are central to risk reduction, yet locally generated evidence from Hafar Al-Batin is limited. Objective: To assess knowledge, attitudes, and preventive practices regarding brucellosis among adults in Hafar Al-Batin and identify sociodemographic and exposure-related predictors of good knowledge and appropriate preventive practices. Methods: An analytical cross-sectional survey was conducted using a structured Arabic electronic questionnaire covering sociodemographic characteristics, awareness and information sources, 15 knowledge items, eight attitude statements, risk exposures, preventive practices, and education preferences. All 544 completed questionnaires were analyzed. Knowledge, attitude, and practice scores were summarized descriptively. Spearman correlation assessed relationships among domain scores, and multivariable binary logistic regression estimated adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for good knowledge and appropriate practice. Results: Among 544 participants, good knowledge was observed in 63.6%, positive attitudes in 60.7%, and appropriate preventive practices in 43.9%. Knowledge and practice were strongly positively correlated (ρ=0.706, p<0.001), while knowledge and attitude were inversely correlated (ρ=-0.398, p<0.001). The attitude–practice correlation was weak and not statistically significant (ρ=0.081, p=0.059). In adjusted analysis, age, education, residence, occupation, animal ownership, and prior awareness were associated with one or both outcomes. Conclusion: Favorable attitudes and moderate awareness coexisted with substantial misconceptions and weak preventive behavior. A locally tailored One Health intervention should prioritize dairy safety, occupational protection, veterinary reporting, and correction of misconceptions, using community meetings, health-center materials, WhatsApp, and healthcare professionals.